Analisis Struktur Balok Sistem Rangka Pemikul Momen Khusus Pada Menara Talawang Kota Palangka Raya - Ilham, Kholik Nur; Baru, Fransisco Happy Riadi Haputra; -, Frieda (CRANE: Civil Engineering Research Journal, 2024)
The Talawang Tower building will be built in the center of the Great Roundabout of Palangka Raya City. The renovation of the Great Roundabout of Palangka Raya, which will be carried out by the Central Kalimantan Provincial Government through the Public Works and Spatial Planning Office (PUPR), will be built grandly with a multipurpose concept. The plan in the middle of the roundabout will be built Talawang Tower with a height of 45 meters. It takes a fairly mature analysis to avoid greater losses, especially earthquake planning analysis. Therefore, the author tries to redesign an earthquake-resistant reinforced concrete structure with an irregular structural model and shows the seismic loads acting on the structure that meets the detaling standards of the Special Moment Bearing Frame System. Planning using SAP2000 by inputting dead loads, live loads, wind loads and earthquake loads to help get the internal forces needed in planning. From the calculation results, a 500 x 650 beam is used with the longitudinal reinforcement requirement of the pedestal to withstand the load is 12D22 with a capacity of ϕMn = 723.955 kN-m > 665.192 kN-m, while the field longitudinal reinforcement requirement is 6D22 with a reinforcement capacity of ϕMn = 379.9872 kN-m > 18.4086 kN-m. The support shear reinforcement requirement is 4D13 - 130 with capacity ϕVn = 753.879 kN > 694.232 kN, while the field shear reinforcement requirement is 2D13 - 150 with capacity ϕVn = 513.47 kN > 405.02 kN.